Combining Tradition and Modernity in the Pesantren-Based Madrasah Curriculum - Sunardi Sunardi; Moch. Sya’roni Hasan; Muhamad Arif; Ari Kartiko; Ahmat Nurulloh (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The background of this research is to understand the curriculum development strategies of pesantren-based madrasahs at MTs Darussalam Ngoro, Jombang. Pesantren play a crucial role in Islamic education in Indonesia, yet integrating pesantren values with the formal curriculum remains challenging. This study aims to identify and analyze the strategies implemented in curriculum development at the madrasah and to evaluate the effectiveness of the curriculum in supporting both learning processes and character development of students. The research employs a descriptive qualitative approach, involving data collection through interviews with the head of the madrasah, the curriculum deputy, and teachers, as well as observations and analysis of madrasah documents such as the academic calendar and curriculum structure. Interviews are conducted in an unstructured format to gain in-depth information, while systematic observations are carried out to understand the dynamics of learning. Documentation is used to gather additional relevant data. The findings indicate that MTs Darussalam Ngoro has successfully integrated pesantren values into the formal curriculum, using strategies such as enhancing the teaching of traditional Islamic texts (kitab kuning), implementing Quran memorization programs (tahfidzul Quran), and developing pesantren-based extracurricular activities. This curriculum effectively supports both learning and character development, positively contributing to Islamic education in Indonesia, and may serve as a model for other pesantren-based madrasahs